Ethics education in MSN programs: a study of national trends. - Burkemper JE; DuBois JM; Lavin MA; Meyer GA; McSweeney M (Nursing Education Perspectives (National League for Nursing))
The aim of this study was to determine the manner in which master's of science in nursing programs, accredited by either the National League for Nursing Accrediting Commission or the Commission on Collegiate Nursing Education, conduct ethics education. A survey method was employed to obtain requisite data. Among the main variables investigated were: the percentage of programs that require a course with formal ethics content; the average number of class hours a program or track dedicates to ethics education; required and actual credentials of instructors who teach ethics; and objectives, topics, teaching methods, and grading methods of required courses with formal ethics content. Results indicated that most programs do not require instructors to have completed formal ethics training. In terms of content, few common trends exist and there are important gaps in clinical ethics topics. Comparisons between school of medicine ethics content reported in the literature and MSN ethics content reported in this study indicate that medical schools are more exacting of their students. The study concludes with a call for the establishment of guidelines or standards relevant to ethics content in MSN curricula in the United States.